Anisakis spp. larvae in three mesopelagic and bathypelagic fish species of the central Mediterranean Sea. Issue 1 (February 2018) - Gaglio, G.; Battaglia, P.; Costa, A.; Cavallaro, M.; Cammilleri, G.; Graci, S.; Buscemi, M.D.; Ferrantelli, V.; Andaloro, F.; Marino, F.
Abstract: In this work 437 fish samples of species belonging to the families Myctophidae ( Electrona risso and Diaphus metopoclampus ) and Phosichthyidae ( Vinciguerria attenuata ) were examined for the presence of Anisakidae larvae. The study was performed with fishes in the central Mediterranean Sea, particularly in the Strait of Sicily and in the Strait of Messina. The visual inspection and chloro-peptic analysis revealed the presence of nematode parasites with prevalence values between 2.9% in Electrona risso samples and 5.4% in Vinciguerria attenuata samples. A positive correlation was found between standard length (SL) and prevalence of infestation in D. metopoclampus samples (p < 0.05). The larvae examined were morphologically ascribed, at genus level, to Anisakis morphotypes I and II and molecularly identified as Anisakis pegreffii, Anisakis ziphidarum and Anisakis physeteris, in 67%, 9% and 24% of the fish samples examined. Overall, A. pegreffii and A. ziphidarum larvae were isolated in 14 and 2 specimens of D. metopoclampus respectively, A. physeteris larvae were found in 3 E. risso and 2 V. attenuata . A positive correlation was found between standard length and prevalence of infestation in D. metopoclampus samples (p < 0.05). First information is provided on the presence of Anisakis spp. larvae of the myctophid fish species E. risso, D. metopoclampus and V. attenuata from the Central Mediterranean. It is also confirmed the role of lanternfishes (Myctophidae) as paratenic hosts for Anisakis spp. Graphical abstract: Image 1 Highlights: A total of 437 Myctophidae and Phosichthyidae fishes were examined for Anisakidae larvae detection. 21 Anisakidae larvae were found, with prevalence values between 2.9% and 5.4%. A positive correlation was found between SL and prevalence in D. metopoclampus samples. No co-infestation with other parasites was found. The work reports for the first time the presence of Anisakidae larvae in the fish species examined.